Chemical disorder determines the deviation of the Slater–Pauling rule for Fe2MnSi-based Heusler alloys: evidences from neutron diffraction and density functional theory. (16th September 2016) - Tedesco, J C G; Pedro, S S; Caraballo Vivas, R J; Cruz, C; Andrade, V M; dos Santos, A M; Carvalho, A M G; Costa, M; Venezuela, P; Rocco, D L; Reis, M S
Abstract: Fe2 MnSi fails to follow the Slater–Pauling rule. This phenomenon is thought to originate from either: (i) an antiferromagnetic arrangement of Mn ions at low temperature and/or (ii) chemical disorder. An important insight on this issue could be achieved by considering Fe2 MnSi1− x Ga x compounds, thoroughly studied here by means of magnetization, neutron diffraction and density functional calculations (DFT). Our results indicate that chemical disorder (and not the antiferromagnetic arrangement) is responsible for the deviation of the Slater–Pauling rule on Fe2 MnSi-based Heusler alloys. Furthermore, evidences suggest that Ga substitution into Si site favors the Fe/Mn disorder, further enhancing the observed deviation.